The effect on the landscape of borrow-pits used in major roadworks - 258677 Sherwood, Philip T.; Roe, P. G.; Transport and Road Research Laboratory (Great Britain) (Crowthorne, Berkshire : Transport and Road Research Laboratory, 1974)
08